Publisher Correction: Stateful characterization of resistive switching TiO2 with electron beam induced currents - Brian D. Hoskins (Nature Portfolio, 2018)
The original version of this Article contained an error in Eq. 1. The arrows between the symbols “T” and “B”, and “B” and “T”, were written “↔” but should have been “→”, and incorrectly read: IEBIC=IEBAC+ISEE+I(e↔h)+IEBICT↔B+IESEEB↔T The correct from of the Eq. 1 is as follows:IEBIC=IEBAC+ISEE+I(e↔h)+IEBICT→B+IESEEB→T This has now been corrected in both the PDF and HTML versions of the article.